Creep mechanical behavior and damage model of layered slate under combined thermal-hydraulic-mechanical action - Haopeng Jiang; Annan Jiang; Fu Zheng (Case Studies in Thermal Engineering, 2024)
The long-term stability of the surrounding rock of geothermal wellbore traversing groundwater and layered rock formations is commonly influenced by the combined effects of thermal, hydraulic, and mechanical factors. In order to mitigate the collapse risk associated with traversing layered rock formations in geothermal wellbore surroundings, this study examines the influence of thermal-hydraulic-mechanical interactions on the creep mechanical characteristics of layered shale. The objective is to provide an assessment of its long-term stability and risk profile. This study focuses on analyzing the creep behavior of layered shale under these combined influences. A nonlinear creep damage model is developed, considering high temperature, pore water pressure, and bedding plane effects through the incorporation of a variable-order fractional element and statistical damage. The variations in model parameters are examined. The findings indicate a gradual decrease in creep mechanical parameters with increasing water pressure and temperature. Additionally, anisotropic behavior is observed in the creep parameters across different angles. The proposed creep damage model shows good agreement with experimental curves, with the fitted parameters exhibiting a linear function relationship with temperature.